EVALUATION OF THE PROGRAM PROVIDING ADDITIONAL INCOME FOR STATE CIVIL APPARATUS TEACHERS IN NORTH MOROWALI DISTRICT - S. Pali, Yunus; Nuraisyah, Nuraisyah; Nur Alamsyah, M.; Haryono, Dandan (Penerbit Lafadz Jaya, 2024)
Additional income is a government program to provide incentive funds to State Civil Service Teachers, where one of the aims is to improve the welfare of ASN Teachers. Through the Minister of Education, Culture, Research and Technology Regulation, number 45 of 2023, the incentive fund provided is IDR. 250,000 / month. This nominal amount, when compared with the incentives received by ASN teachers who receive professional allowances, is very different, even though the workload for both is the same. This research uses a descriptive approach with qualitative research methods. Meanwhile, the informants for this research were ASN teachers who received additional income programs, Heads of Departments and Secretaries of the Regional Education and Culture Service of North Morowali Regency. The data analysis used is Data Condensation, Data Presentation, and Conclusion Drawing. The evaluation indicators used in this research are Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy of the program. The conclusion of this research, if viewed from these indicators, is that aspects of effectiveness, efficiency and responsiveness have gone well. However, the aspects of adequacy, alignment and accuracy are not considered good, especially when looking at the achievement of educational goals as mandated by law number 45 of 2023.